PERBEDAAN PENGARUH PAPARAN MUSIK MOZART, BEETHOVEN, DAN CHOPIN SELAMA KEBUNTINGAN TERHADAP KEPADATAN DENDRIT DI CEREBELLUM Rattus norvegicus BARU LAHIR - Ancha Ayu Amishinta; Hermanto Tri Joewono; widjiati Widjiati (NHM PRESS, 2018)
Indonesia is categorized as middle humandevelopment index. One of the causes is the fluentignorance of brain growth and development during1000 days of life period. This period is the bestopportunity to give proper stimulations to increase themaximal brain growth and development. Exposure toclassical music such as Mozart, Beethoven, andChopin music can increase the wave of brain activity.During pregnancy, Mozart music is proven to increasethe dendritic density. Analyzing the difference ofdendritic density of cerebrum and cerebellum ofnewborn baby of Rattus norvegicus that are exposedto the Mozart, Beethoven, and Chopin music, and thatis not exposed to music during pregnancy. Laboratoryexperimental research, posttest-only control groupdesign. Subjects were female pregnant Rattusnorvegicus, grouped into 4 random groups: 1 controlgroup and 3 treatments groups; with 6 samples each.Subjects were super ovulated, and 65 dB intensity ofmusic was played for an hour at 20.00-21.00 on thesubjects on 10th day of pregnancy. On 20th day ofpregnancy, the mothers were dissected usingcaesarean section. 2 heaviest newborn babies ofRattus norvegicus were taken, and their brain tissueswere taken as samples. The dendritic density ofcerebrum and cerebellum were observed using GolgiCox method of silver impregnationprocedure.Statistical test concluded there weresignificant differences of dendritic density of cerebrumand cerebellum of newborn babies of Rattusnorvegicus among the exposure to Mozart,Beethoven, and Chopin music, and without theexposure to music with value of p=0,004 (<0,05) incerebrum and p=0,003 (<0,05) in cerebellum. Thedendritic density of cerebrum and cerebellum ofnewborn babies of Rattus norvegicus that wereexposed to Mozart music during pregnancy werehigher than that are exposed to Beethoven andChopin music and that were not exposed to music. Itis recommended for the next research to do furtherresearch to prove the dendritic density caused by themusical stimulation during pregnancy when Rattusnorvegicus grows up.